Faktor-Faktor Yang Memengaruhi Kualitas Hidup Pada Penderita Diabetes Melitus Tipe 2 - Rosliana dewi -; Novi Puspita Darmawan; Salma Aiska Nayla; Bunga Ayu Tresna; Salsadila; Johan Budhiana (Jurnal Kesehatan Mahardika, 2026)
Introduction: NCDs including diabetes are becoming an increasingly urgent health problem worldwide and in Indonesia. DMT2 can reduce quality of life through various complications, so it is important to understand the role of coping mechanisms, stress, self-care, and religiosity in supporting the well-being of DMT2 patients. This study aims to determine the factors that affect quality of life in DMT2 patients. Method: This was a correlational study with a cross-sectional approach. The population consisted of people with T2DM, with a sample of 162 people using proportional random sampling. Data collection methods included the TBCI, DDS, SDSCA, MUDRAS, and DQOL questionnaires. Multiple linear regression was used for statistical analysis. Result: The results showed that there was a significant simultaneous influence of coping mechanisms, stress, self-care, and religiosity on the quality of life of DMT2 patients (p < 0.05). Conclusion: There was a significant simultaneous influence of coping mechanisms, stress, self-care, and religiosity on the quality of life of DMT2 patients. It is recommended that non-pharmacological interventions targeting coping mechanisms, stress, self-care, and religiosity be developed to improve the quality of life of DMT2 patients.